2020
DOI: 10.1016/j.cgh.2019.08.030
|View full text |Cite
|
Sign up to set email alerts
|

Expression Levels of 4 Genes in Colon Tissue Might Be Used to Predict Which Patients Will Enter Endoscopic Remission After Vedolizumab Therapy for Inflammatory Bowel Diseases

Abstract: BACKGROUND & AIMS: We aimed to identify biomarkers that might be used to predict responses of patients with inflammatory bowel diseases (IBD) to vedolizumab therapy. METHODS: We obtained biopsies from inflamed colon of patients with IBD who began treatment with vedolizumab (n [ 31) or tumor necrosis factor (TNF) antagonists (n [ 20) and performed RNA-sequencing analyses. We compared gene expression patterns between patients who did and did not enter endoscopic remission (absence of ulcerations at month 6 for p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
49
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 63 publications
(49 citation statements)
references
References 33 publications
0
49
0
Order By: Relevance
“…We believe further studies will help us decipher key predictors of response within the identified direct mechanisms of action that, in a manner similar to predictors, should be unique to each specific drug type. 54 …”
Section: Discussionmentioning
confidence: 99%
“…We believe further studies will help us decipher key predictors of response within the identified direct mechanisms of action that, in a manner similar to predictors, should be unique to each specific drug type. 54 …”
Section: Discussionmentioning
confidence: 99%
“…While several potential biomarkers have been reported [19][20][21], such approaches require further validations before entering clinical practice. To the contrary, clinical characteristics of patients are easy to collect and may directly help to estimate outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, in UC patients non-responsive to anti-α4β7 treatment, we observed reduced M2 macrophage levels. Verstockt et al transcriptomic analysis of UC tissue from patients prior to receiving biologic therapy revealed significant enrichment of immune cells in non-responders including M1 macrophages and Tregs, while responders had elevated naïve B cells 65 . Our CIBERSORT analysis also showed a trend in elevated M1 macrophages, while changes in Tregs were insignificant.…”
Section: Discussionmentioning
confidence: 99%